A vállalati képzés-fejlesztés szerepe a döntéshozatalban : A 2021-es CRANET felmérés alapján - Bachmann-Matisa, Júlia (Közép-Európai Közlemények, 2025)
Training and development, as one of the most important functions of HR, can be an important indicator in the life of an organisation, especially if it is consciously planned and organised by decision-makers. The CRANET survey aims to gather information on human resource management (HRM) practices and their changes in different countries, making it one of the key studies whose results not only provide a basis for comparison based on objective measurements, but also allow further lessons to be drawn, especially for the Hungarian context. Within the questionnaire, the training and development aspect appears in several sections. Focusing on staff development, I sought to identify a statistically verifiable correlation between the subsections of development and career management methods and the decisionmakers responsible for training development: the focus of my investigation was the assumption that it does not matter who the main decision-maker is: the less the manager decides on training development issues, the more the organisation decides to apply development and career management methods.